A Synthesis of Deepwater Horizon Impacts on Coastal and Nearshore Living Marine Resources - Murawski, Steven A.; Kilborn, Joshua P.; Bejarano, Adriana C.; Chagaris, David; Donaldson, David; Hernandez, Frank J.; MacDonald, Timothy C.; Newton, Craig; Peebles, Ernst; Robinson, Kelly L. (Frontiers in Marine Science, 2021)
The 2010 Deepwater Horizon (DWH) oil blowout in the Gulf of Mexico began on April 20, originating in the deepsea 66 km off the Louisiana coast. By early June, DWH oil had spread to coastal Louisiana, Mississippi, Alabama and western Florida. An estimated 2,113 km of shoreline were oiled, making DWH the largest marine oil spill in global history by length of affected shoreline. Additionally, a series of oil spill response measures were deployed, including diversions of Mississippi River discharge to forestall oil coming ashore, and the establishment of large-scale fishery closures, with both affecting coastal resources to varying degrees. Here we review published studies and describe additional analyses evaluating long-term impacts of DWH on coastal/nearshore biological resources. We assembled time series data collected by state, federal and academic partners on population abundance and environmental conditions to evaluate species and community change. Our study focused on plankton, invertebrates, fishes and dolphins, and 13 “key species” were selected to conduct semi-quantitative vulnerability-resilience (V-R) analyses. At one extreme, early life stages of Gulf Menhaden (Brevoortia patronus) were not affected due to seasonal spawning and larval development preceding the spill. In contrast, demographically independent populations of the common Bottlenose Dolphin, (Tursiops truncatus) suffered a variety of severe and ongoing health effects owing to oil exposure. Virtually all of the heavily oiled salt marsh habitat was in Louisiana; the majority occurring in Barataria Bay. Multispecies trawl survey abundances declined post-DWH throughout eastern coastal Louisiana but remained stable elsewhere. A regime shift in composition of Barataria Bay trawl survey catches occurred during and following the spill, the persistence of which was associated with long-term reductions in average salinity and increases in water clarity. In some cases, fishery closures were associated with measurable but ephemeral increases in abundance of some targeted and bycatch species. Freshwater flooding of marshes was ineffective in preventing coastal oiling and severely affected benthic euryhaline resources including Eastern Oyster (Crassostrea virginica) and Marsh Periwinkle (Littoraria irrorata). The flooding response measure experiment also indicates the directionality of impacts that further planned water diversions may have on ecological communities of lower Mississippi River basins.